Development of a set of patient reported outcome measures for patients with benign liver tumours and cysts: patient focus groups and systematic review - Alicia Furumaya; Lynn E. Nooijen; Martijn P. D. Haring; Hedy A. van Oers; Marlou van Beneden; Belle V. van Rosmalen; R. Bart Takkenberg; Geert Kazemier; Marc G. Besselink; Vincent E. de Meijer; Joris I. Erdmann; the Dutch Benign Liver Tumor Group (SpringerOpen, 2022)
Abstract Background Patient reported outcome measures (PROMs) may be useful for patients with benign liver tumours and cysts (BLTC) to evaluate the impact of treatment and/or guide shared decision making. Yet, a set of PROMs relevant to patients with BLTC is currently unavailable. In this study, we selected a PROMs set for patients with BLTC. Methods Potentially relevant patient reported outcomes (PROs) were selected by psychologist-researchers based on keywords used or suggested by participants of two virtual focus groups meetings consisting of thirteen female BLTC patients with a median age of 50 years. Subsequently, patients were asked to report their most relevant PROs. PROMs identified by systematic literature review and computerized adaptive tests (CATs) in the Patient-Reported Outcomes Measurement Information System (PROMIS) were considered in selecting the final PROMs set to assess relevant outcomes. Results The most important PROs were: insecurity/anxiety (11/12 patients), pain (9/12 patients), fatigue (8/12 patients), and limitations in daily life (5/12 patients). The literature review included 23 studies, which used various generic and disease-specific PROMs, often not measuring (all) relevant PROs. The final selected PROMs set included numerical rating scales for pain, two questions on overall health and quality of life and four PROMIS CATs. Conclusions A PROMs set generically and efficiently measuring outcomes relevant for patients with BLTC was developed and may be used in future research and clinical practice.